Improving diet quality and micronutrient nutrition: Homestead food production in Bangladesh - Iannotti, Lora L.; Cunningham, Kenda; Ruel, Marie T. (International Food Policy Research Institute, 2009)
A critical yet often overlooked component of food security is diet quality. Even households who have access to sufficient amounts of food and calories may still lack essential micronutrients, increasing their risk for both short- and long-term health and development consequences. Interventions that address poor diet quality and related deficiencies of vitamin A, zinc, iron, among others, are important for achieving full food security in vulnerable populations. The homestead food production (HFP) program, introduced in Bangladesh by Helen Keller International nearly two decades ago, promotes an integrated package of home gardening, small livestock production and nutrition education with the aim of increasing household production, availability, and consumption of micronutrient-rich foods and improving the health and nutritional status of women and children. Implemented by NGO partners and the Government of Bangladesh, HFP has expanded its reach into over one half of the country’s subdistricts and is now operating in several countries of Asia and Sub-Saharan Africa. Evidence shows that HFP in Bangladesh has improved food security for nearly 5 million vulnerable people in diverse agroecological zones. This has been achieved through: increased production and consumption of micronutrient-rich foods; increased income from gardens and expenditures on micronutrient-rich foods; women’s empowerment; enhanced partner capacity; and community development.